PENGARUH AKTIVITAS PENGASUHAN CUCU TERHADAP FUNGSI KOGNITIF PADA PEREMPUAN LANSIA - Frederica Jovianti; Linda Suryakusuma; Yuda Turana; Yvonne Suzy Handajani (PERDOSNI, 2018)
THE IMPACT OF GRANDPARENTING ACTIVITY ON COGNITIVE FUNCTION IN ELDERLY WOMANABSTRACT Introduction: Cognitive impairment is a neurodegenerative process which often experienced by the elderly. One of the factors associated with cognitive function is grandparenting which is common and has become a social norm in Indonesia.Aims: To determine the association between characteristics of the subjects and grandparenting activity with cognitive function in elderly woman.Methods: This study was conducted on July 2016–January 2017 in West Jakarta and as a part of Active Ageing Research in Atma Jaya University. The data were collected through grandparenting activity questionnaire and cognitive function assessment using Mini Mental State Examination (MMSE).Results: Based on 93 participants, the age mean was 67,51±5,058 and majority had education <9 years (54,8%). Data analysis showed that education, grandparenting, the quality of grandparenting, types of grandparenting activity specifically preparing food and/or feeding child and storytelling had a significant association with global cognitive function.Discussions: Physical, social activity, and cognitive stimulation while caring for grandchildren can prevent decline in cognitive function.Keywords: Elderly, cognitive function, grandparentingABSTRAK Pendahuluan: Penurunan fungsi kognitif merupakan suatu proses neurodegeneratif yang sering dialami oleh lansia. Salah satu faktor yang dianggap berpengaruh terhadap fungsi kognitif adalah aktivitas pengasuhan cucu yang masih umum dilakukan dan telah menjadi bagian dari norma masyarakat di Indonesia.Tujuan: Mengetahui hubungan antara karakteristik subjek dan aktivitas pengasuhan cucu terhadap fungsi kognitif pada perempuan lansia.Metode: Penelitian dilakukan pada bulan Juli 2016–Januari 2017 di Jakarta Barat dan merupakan bagian dari penelitian Active Ageing di Universitas Atma Jaya. Pengumpulan data dilakukan melalui pengisian kuesioner aktivitas pengasuhan cucu dan pengukuran fungsi kognitif menggunakan Mini Mental State Examination (MMSE).Hasil: Penelitian terhadap 93 subjek dengan rerata usia 67,51±5,058 dan sebagian besar berpendidikan <9 tahun (54,8%). Pendidikan, aktivitas pengasuhan cucu, kualitas pengasuhan cucu, serta jenis aktivitas pengasuhan cucu, yaitu menyiapkan dan/atau menyuapi makanan dan membacakan cerita memiliki hubungan yang bermakna dengan fungsi kognitif global.Diskusi: Aktivitas fisik, sosial dan stimulasi kognitif pada saat mengasuh cucu dapat mencegah terjadinya penurunanfungsi kognitif.Kata kunci: Aktivitas pengasuhan cucu, fungsi kognitif, lanjut usia